Fundamental analysis and securities investment in Vietnam - Dang, Tran Phuc (ĐHQG, 2016)
Objectives: - Systematizing the fundamental analysis methods in securities investment. - Assessing, selecting the fundamental analysis methods applied on Vietnam's stock market. - Introducing new method of analyzing and evaluating stocks which is more simple and suitable for minority investors. - Applying fundamental analysis methods to price five stocks listed on Stock Exchange of HSX. Main contents: In addition to the introduction, conclusion and list of references, the research topic consists of four chapters: Chapter 1: The concept of securities analysis and investment and analysis tools of securities investment. Chapter 2: Fundamental analysis and several basic methods of stock pricing in the world, Standard and Poor's Equity Research Methodology. Chapter 3: Practices of stock pricing by fundamental analysis methods in Vietnam at present, propose new methods of analyzing and evaluating new stocks. Chapter 4: Apply to analyzing some real estate stocks Results obtained:The research has achieved the objectives and mission proposed: - Give a system of fundamental analysis methods in securities investment in the world and in Vietnam. - Introduce and analyze new method of analyzing and evaluating stocks in securities investment with practical illustrations which are easy to understand. - Obtain a complete analysis sample in securities analysis and investment which help investors get access to analysis and investment process through the analysis of five real estate stocks listed.